The multilingual nature of dopamine neurons - Trudeau, Louis-Eric (Prog Brain Res, 2014)
The ability of dopamine (DA) neurons to release other transmitters in addition to DA itself has been increasingly recognized, hence the concept of their multilingual nature. A subset of DA neurons, mainly found in the ventral tegmental area, express VGLUT2, allowing them to package and release glutamate onto striatal spiny projection neurons and cholinergic interneurons. Some dopaminergic axon terminals release GABA. Glutamate release by DA neurons has a developmental role, facilitating axonal growth and survival, and may determine in part the critical contribution of the ventral striatum to psychostimulant-induced behavior. Vesicular glutamate coentry may have synergistic effects on vesicular DA filling. The multilingual transmission of DA neurons across multiple striatal domains and the increasing insight into the role of glutamate cotransmission in the ventral striatum highlight the importance of analyzing DA neuron transmission at the synaptic level.